The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3340/jkns.2009.46.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Intradural Lumbar Disc Herniations Associated with Epidural Adhesion : Report of Two Cases

Abstract: J Korean Neurosurg Soc 46 : [168][169][170][171] 2009 Intradural lumbar disc herniation (ILDH) is rare. In this report, authors present 2 cases of ILDHs associated with severe adhesion between the dural sac and posterior longitudinal ligament. In a 40-year-old man, ILDH occurred in association with epidural adhesion due to ossification of the posterior longitudinal ligament (OPLL). In other 31-year-old man, ILDH occurred in presence of epidural adhesion due to previous spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…Other predisposing conditions stated in the literature are congenital reduction of dural thickness, vertebral canal congenital stenosis [1], and previous surgeries [10]. All five cases reported in this paper presented adhesions between the dural sac and the PLL, and one case had previous surgery at the same level of the IDH.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Other predisposing conditions stated in the literature are congenital reduction of dural thickness, vertebral canal congenital stenosis [1], and previous surgeries [10]. All five cases reported in this paper presented adhesions between the dural sac and the PLL, and one case had previous surgery at the same level of the IDH.…”
Section: Discussionmentioning
confidence: 87%
“…Such adhesions occur more often in L4-L5 space, which justifies a higher incidence of intradural disc herniations at this level, being more prevalent in patients with history of previous lumbar pain [6]. One believes that patients with degenerative disc pathologies would present a chronic inflammatory process, which would favor the occurrence of these adhesions, leading to erosions on the adjacent dural sheath [7][8][9][10][11]. Nevertheless, IDH can have congenital origin: such adhesions have also been found in stillborn autopsies [4,7].…”
Section: Discussionmentioning
confidence: 99%
“…These dense adhesions may be congenital due to prenatal adhesion formation [17] or they are acquired and occur (1) spontaneously subsequent to degenerative disc disease with or without association to an ossification of the PLL [7] or they (2) develop after the previous spine surgery or trauma due to scar tissue formation within the epidural space [2,7,15].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report of an intradural sequester was presented by Dandy [4] in 1942, more than 140 cases have been reported in the literature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the authors reported that adhesion between the dura mater and posterior longitudinal ligament causing from previous spine surgery has been accepted as a predisposing factor [1]. Here we report an adult patient with IDLDH.…”
Section: Introductionmentioning
confidence: 86%